Santo Toribio´s apllication for peruvian religious heritage - Benito Rodríguez, José Antonio (2013)
When Juan Pablo II came to Peru, his central conference for the Peruvian bishops was about the four stagesof St. Toribio: his life of holiness, his commitment in the complete education of natives, his commitmentto integration and communion and his close relationship with the papacy. The fourth are like pillars of hismission and vocations of the Peruvian church builder. This holy father of the American Church, in wordsof his first biographer Leon Pinelo: “he didn’t’ waste his time” and he began working the Church, whichhe called “the new Christendom of the Indies”. Thirteen diocesan synods, three provincial councils withhis catechetical instruments such as the Trilingual Catechism (in Spanish, Quechua and Aymara) andthe Pastoral visits. Instigator of institutions such as the Santa Clara Seminary or Convent, organizationsas a new association, parishes and towns .During 25 years, they laid the basis of the current Peruvianreligious heritage. This heritage is reflected in the culture of holiness of his contemporaries such as Roseof Lima and Martin who St. Toribio confirmed, Juan Macias, Francisco Solano and a lot of Blessedand servants of god who he also helped. But also St. Toribio helped in the building of churches likethe Cathedral, Convents such as Santa Clara and the numerous parishes and chapels, fraternities anddoctrines, dispersed throughout all his archbishop territory.